ANALISIS GESTURE GURU DALAM PEMBELAJARAN MATEMATIKA KELAS IV SDN SUMBER 03 KABUPATEN BLITAR - Dena Ade Primasari; Dyah Worowirastri Ekowati; Arina Restian (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
One of the teacher's strategies in delivering communication is through gestures. Gestures are a form of nonverbal communication expressed through body movements to convey messages alongside speech. This study aims to analyze the use of teacher gestures in mathematics learning in Grade IV at SDN Sumber 03, Blitar Regency. The success of learning depends on the teacher's communication skills in delivering material. Through gestures, teachers are expected to create an enjoyable mathematics learning atmosphere and enhance students' enthusiasm for learning. This research uses a qualitative approach with a descriptive type. The research subjects were Grade IV teachers at SDN Sumber 03, Blitar Regency. Data collection techniques included observation, interviews, and documentation in the form of audiovisual recordings and photographs. Data sources consisted of primary data (results of observations and interviews) and secondary data (documentation). Data analysis involved three stages: data reduction, data presentation, and conclusion drawing. Data validity was ensured through triangulation techniques. This research was conducted during the even semester of the 2024/2025 academic year. The research findings indicate that the teacher used three types of gestures according to Alibali & Nathan's modification of McNeill’s classification: pointing gestures (88 times), representational gestures (22 times), and writing gestures (16 times) in teaching equivalent fractions in mathematics. The pointing gesture was the most dominant type used. Appropriate use of gestures can increase student engagement in the learning process and help them better understand the concepts being taught